Impact of Medical Student Involvement on Emergency Department Outcomes: A Tertiary Center Analysis - Ryan Ballard; Asfia Qureshi; Chengu Niu; Keith Grams; Mathew Devine; Nagesh Jadhav; Richard Alweis (Western Journal of Emergency Medicine)
Introduction: Increasing patient use of emergency departments (ED) and overcapacity threaten both efficiency of the care provided and the teaching mission. We investigated the influence of medical student (MS) involvement on ED throughput, resource use, and clinical outcomes, and we addressed gaps in existing literature that primarily focus on resident physicians and singular throughput metrics. Methods: We conducted a retrospective observational analysis of 123,503 encounters with patients >21 years of age at an urban, tertiary-care hospital, comparing cases with and without MS participation. We excluded patients seen by advanced practice practitioners. We compared continuous variables using t-tests with bootstrap, and categorical variables by chi-square tests. Continuous variables were reported with mean and standard deviation. Results: We analyzed patient encounters both with and without MS coverage across various complexity levels from January 1, 2022–December 31, 2023. Of the 123,503 patient encounters, 9,635 (7.8%) involved MS participation, and 113,868 (92.2%) did not. Across all encounters, door-to-physician time showed no significant difference between encounters with (28.1 minutes ± 38.6) and without medical students (28.4 minutes ± 38.0; P = .435), while door-to-triage and arrival-to-disposition time (292.6 minutes ± 193.7 vs 270.4 minutes ± 532.8; P < .001) and doctor-to-disposition time (266.8 minutes ± 186.1 vs. 242.9 minutes ± 376.4; P < .001) were significantly longer. In high-complexity encounters, patients seen with medical students experienced shorter door-to-physician (26.6 vs 28.2 minutes, P < .001), door-to-triage (13.6 vs 14.5 minutes, P = .03), arrival-to-disposition (301.1 vs 307.7 minutes, P = .02), and doctor-to-disposition times (275.2 vs 281.3 minutes, P =.02). Conclusion: We found that medical student involvement is associated with longer patient stays in low- to medium-complexity cases but improved efficiency in the management of high-complexity cases. Increased rates of some diagnostic imaging and higher admission rates occurred with medical students. Our single-center design highlights the need for multicenter validation of these findings to inform future resource allocation and educational strategies in the ED.